Maternal high‐salt diet altered PKC/MLC20 pathway and increased ANG II receptor‐mediated vasoconstriction in adult male rat offspring. Issue 7 (4th May 2016) - Li, Weisheng; Lv, Juanxiu; Wu, Jue; Zhou, Xiuwen; Jiang, Lin; Zhu, Xiaolin; Tu, Qing; Tang, Jiaqi; Liu, Yanping; He, Axin; Zhong, Yuan; Xu, Zhice
Abstract : The present study shows that maternal high‐salt diet could affect the development of the coronary artery, with altered vascular functions in the offspring such as the increased Angiotensin II‐mediated vasoconstrictions. The Angiotensin II receptor type 1–PKC‐20KDa myosin light chain phosphorylation pathway may be the possible underlying mechanism. The data gained provide new information for early prevention of cardiovascular diseases in developmental origins. Abstract : Scope: High‐salt diet (HSD) is associated with cardiovascular diseases. This study aims at ascertaining the influence of maternal HSD on offspring's angiotensin II (ANG II)‐mediated vasoconstriction and the underlying mechanisms. Methods and results: In comparison to a normal‐salt diet, HSD used in pregnancy in rats changed the ultrastructures of the coronary artery (CA) in 5‐month‐old male offspring, and increased ANG II‐mediated CA contractility. Measurement of [Ca 2+ ]i in CA using fluorescent fura‐2, a Ca 2+ indicator, showed that ANG II‐mediated increases in [Ca 2+ ]i were the same between HSD and normal‐salt diet groups, but the ratio of diameter change/[Ca 2+ ]i induced by ANG II were significantly higher in HSD groups. Angiotensin II receptor type 1, not angiotensin II receptor type 2, caused ANG II‐mediated vasoconstriction. Protein kinase C (PKC) inhibitor GF109203X attenuated the ANG II‐mediated vasoconstriction, PKC agonist phorbol12, 13‐dibutyrate produced a greater contraction. There was an increase in PKCβ mRNA and the corresponding protein abundance in the offspring, whereas other PKC subunits PKCα, PKCδ, and PKCε did not change. Moreover, 20 kDa myosin light chain phosphorylation levels were increased in HSD group. Conclusion: Maternal HSD affected the developmental programing for the offspring CA, with increased ANG II‐mediated vasoconstrictions. The angiotensin II receptor type 1‐PKC‐20 kDa myosin light chain phosphorylation pathway was the possible mediated cellular mechanism.